Complex torcular dural arteriovenous fistula leading to cortical venous reflux-induced severe varix and subsequent bilateral cerebral hemispheric hemorrhage: a case report - Li, Ziqi; Hou, Pengwei; Chen, Qizuan; Mu, Shuwen; Li, Jun; Fang, Yi; Jiang, Wenting; Tian, Xinhua; Wang, Shousen (Frontiers in Neurology, 2023)
Background and Importance: Dural arteriovenous fistulas (dAVFs) with cortical venous reflux (CVR) are associated with a higher incidence of intracranial hemorrhage (ICH). We report the first case a rare case of a complex torcular dAVF with severe cortical veins (CV) varix leading to extensive bilateral cerebral hemorrhages. This discovery suggests a potential new subtype of dAVF. The case underscores the necessity of a comprehensive understanding of hemodynamic changes in dAVFs and the importance of considering venous compensatory capacity in treatment. This case challenges existing classifications and treatment strategies for dAVFs, highlighting the need for further research and discussion within the neurosurgical community.